2022
DOI: 10.3390/cells11172666
|View full text |Cite
|
Sign up to set email alerts
|

Akkermansia muciniphila Reduces Peritonitis and Improves Intestinal Tissue Wound Healing after a Colonic Transmural Defect by a MyD88-Dependent Mechanism

Abstract: Anastomotic leakage is a major complication following colorectal surgery leading to peritonitis, complications, and mortality. Akkermansia muciniphila has shown beneficial effects on the gut barrier function. Whether A. muciniphila reduces peritonitis and mortality during colonic leakage is unknown. Whether A. muciniphila can directly modulate the expression of genes in the colonic mucosa in humans has never been studied. We investigated the effects of a pretreatment (14 days) with live A. muciniphila prior to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 65 publications
0
6
0
Order By: Relevance
“…By using an organoid cell-culture model, we demonstrated that HD5 1–9 and hBD2 induce HDPs through the Myd88 signaling pathway in vitro. Recent studies revealed that bacterial-mediated regulation of HDP expression occurs in a TLR/Myd88-dependent manner [ 71 , 72 ]. Thus, microbiota-free, TLR- or Myd88-deficient mice exhibited decreased Defa5 mRNA expression, which was recovered by treating with Lactobacillus lactis or TLR agonists [ 73 ].…”
Section: Discussionmentioning
confidence: 99%
“…By using an organoid cell-culture model, we demonstrated that HD5 1–9 and hBD2 induce HDPs through the Myd88 signaling pathway in vitro. Recent studies revealed that bacterial-mediated regulation of HDP expression occurs in a TLR/Myd88-dependent manner [ 71 , 72 ]. Thus, microbiota-free, TLR- or Myd88-deficient mice exhibited decreased Defa5 mRNA expression, which was recovered by treating with Lactobacillus lactis or TLR agonists [ 73 ].…”
Section: Discussionmentioning
confidence: 99%
“…IL-22 production is also associated with epithelial regeneration and repair. Akkermansia muciniphila , a common human gut bacterium, has been shown to induce IL-22 production by ILC3 cells ( Bachmann et al, 2022 ; Zheng et al, 2023 ). Interferon gamma (IFN-γ) production is a typical response of Th1 cells and is associated with protective immunity against intracellular pathogens.…”
Section: Gut Microbiota and Cytokine Modulationmentioning
confidence: 99%
“… 11 In addition, it is already known that A. muciniphila interaction with the host involves TLR2-signaling pathways 19 , 43 and modulation of IL-10 and IL-22 cytokines. 44 , 45 Thus, a moderately induced colonic expression of IL-22 by pasteurized A. muciniphila would restore, at least in part, colonic sensitivity and normal animal behavior in our two IBS-like mouse models.…”
Section: Discussion/conclusionmentioning
confidence: 80%